Evaluation of heavy metal contamination of soil and the health risks in four potato-producing areas - Zhang, Jie; Liu, Ke; He, Xue; Li, Wei; Zhang, Meng; Cai, Quan (Frontiers in Environmental Science, 2023)
A total of 89 soil samples were collected from four potato-producing areas (Libo, Chishui, Panxian and Weining) in Guizhou Province, China, the concentrations of Cr, Mn, Ni, Cu, Zn, As, Cd, Sb and Pb were analyzed and determined to study the risk of heavy metals in the soil. The evaluation of heavy metal pollution in the soil was based on the geo-accumulation index, pollution load index, and health risk evaluation methods. Libo and Chishui were generally non-pollution, and some elements in Panxian and Weining were polluted. In terms of carcinogenesis, the risk of human carcinogenesis in each study area under the hand mouth pathway was Cr > As > Cd; Under the skin route, Cr and As would be produced certain carcinogenic risk to human; Under the respiratory route, Cr had a strong carcinogenic risk to adults; In terms of non-carcinogenesis, children in each study area had a strong non-carcinogenic risk under the three pathways; The risk of adults under the respiratory route of carcinogenic evaluation was greater than that of children, and the risk of children under the hand, mouth, skin route and non carcinogenic evaluation was greater than that of adults. Panxian and Weining were heavily polluted by heavy metals, while Libo and Chishui were less polluted. Heavy metals in the soil of the four study areas would be posed health risks to human beings. Attention should be paid to the remediation and treatment of heavy metals in the soil of polluted areas to ensure human health.